2016
DOI: 10.1073/pnas.1515465113
|View full text |Cite
|
Sign up to set email alerts
|

Polycomb inhibits histone acetylation by CBP by binding directly to its catalytic domain

Abstract: Drosophila Polycomb (PC), a subunit of Polycomb repressive complex 1 (PRC1), is well known for its role in maintaining repression of the homeotic genes and many others and for its binding to trimethylated histone H3 on Lys 27 (H3K27me3) via its chromodomain. Here, we identify a novel activity of PC: inhibition of the histone acetylation activity of CREB-binding protein (CBP). We show that PC and its mammalian CBX orthologs interact directly with the histone acetyltransferase (HAT) domain of CBP, binding to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 68 publications
0
33
1
Order By: Relevance
“…Interestingly, our data revealed that H3K27me3 was positively correlated with Pol II-Ser5P in both NPCs and neurons. In this regard, it is intriguing to note that Drosophila PRC (Polycomb-repressive complex) could physically interact with paused Pol II (Tie et al, 2016) and was preferentially localized to paused promoters (Enderle et al, 2011). In addition, between the two classes of bivalent domains in embryonic stem cells (Ku et al, 2008), it was found that promoters bound by PRC2 alone could allow Pol II pausing (Min et al, 2011), although PRC1 and PRC2 co-occupied promoters were devoid of paused Pol II.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, our data revealed that H3K27me3 was positively correlated with Pol II-Ser5P in both NPCs and neurons. In this regard, it is intriguing to note that Drosophila PRC (Polycomb-repressive complex) could physically interact with paused Pol II (Tie et al, 2016) and was preferentially localized to paused promoters (Enderle et al, 2011). In addition, between the two classes of bivalent domains in embryonic stem cells (Ku et al, 2008), it was found that promoters bound by PRC2 alone could allow Pol II pausing (Min et al, 2011), although PRC1 and PRC2 co-occupied promoters were devoid of paused Pol II.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, PcG proteins bind directly to the acetyltransferase CREB-binding protein (CBP), and inhibit its catalytic activity towards H3K27 [43]. Together, these events maintain local chromatin compaction precluding the transcription of target genes (Figure 2A).…”
Section: Polycomb Group Complexes Regulate Chromatin At Different Scalesmentioning
confidence: 99%
“…Mouse postnatal cardiomyocites display Eed interaction with HDACs, enhancing their catalytic activity; this novel Eed function is an H3K27me3 independent repressive mechanism, crucial for physiological heart function . Similarly in Drosophila, Pc has been demonstrated to interact with the CREB‐binding protein (CBP) acetyl transferase, inhibiting its histone acetyltransferase activity …”
Section: Nuclear Prcs Reveal Unpredicted Interactors and Functionsmentioning
confidence: 99%